ANALISIS KINERJA PROGRAM ALOKASI DANA DESA PROPOSIONAL DI DESA MAYANG KECAMATAN KELAPA KAMPIT KABUPATEN BELITUNG TIMUR - , Ronny Setiawan, Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A breakthrough issued in 2006 by East Belitung Regency Administration is a policy about proportional allocation of village funds (ADDP). It focused / emphasised on pioneering and development activities of community economic business and the expansion of employment opportunities targeted on unemployers, pieceworkers, and casual workers. The objectives of ADDP policy are: First, to reduce and if possible eliminate the dependence of local revenue sources and community economic business on the the mining sector. Second, to prevent the environmental damage getting worse. Third, to secure the ownership of strategic regional assets such as land and water from exploitation activities of large companies as well as to expand the capital access, market and information to the community. In fact, there are obstacles faced by this program, such as: some failed businesses types, the public dissatisfaction, criticism of the legislature or not getting the full cross-sector bureaucracy support. In the authorâs point of view, those are very intrigued. It is very important to evaluate the actual ADDP policy performance in East Belitung Regency Administration by taking case study covering Mayang Village